Resource specialisation and the divergence of killer whale populations - A. R. Hoelzel; Andre Moura (2015)
Individual resource specialisation is common in natural populations associated with competition and ecological opportunity (see Aroujo et al., 2011), and well known for the killer whale (where social groups specialise) and other delphinid cetaceans (see Hoelzel, 2002). Prey choice affects a predator’s temporal and spatial pattern of habitat use. For the killer whale, social groups (pods) learn where prey resources are seasonally abundant, and the techniques required to exploit different resources efficiently. Some fish prey, especially anadromous species such as salmon, may provide predictable seasonally rich concentrations, whereas marine mammal prey may be more patchily distributed and show a different pattern of temporal abundance (and accessibility). However, these resources are found within the same waters, though the timing and technique for capture may differ. Foote and Morin (2015) suggest that the co-occurrence of populations in the same ocean doesn't necessarily imply that they differentiated in sympatry, which is clearly true. However, as Moura et al. (2015) and others (for example, Hoelzel et al., 1998, 2007) have discussed, it is the life history and behaviour of killer whales that suggest the potential for differentiation in sympatry. Although the proximity of resources brings killer whale pods into sympatry, the differential pattern of spatial and temporal habitat use, as well as fidelity to pods that forage by similar learned methods, could serve to isolate resource specialist communities reproductively.